2014
DOI: 10.1007/s00438-014-0963-9
|View full text |Cite
|
Sign up to set email alerts
|

A comparative meta-analysis of QTL between intraspecific Gossypium hirsutum and interspecific G. hirsutum × G. barbadense populations

Abstract: Based on 1075 and 1059 QTL from intraspecific Upland and interspecific Upland × Pima populations, respectively, the identification of QTL clusters and hotspots provides a useful resource for cotton breeding. Mapping of quantitative trait loci (QTL) is a pre-requisite of marker-assisted selection for crop yield and quality. Recent meta-analysis of QTL in tetraploid cotton (Gossypium spp.) has identified regions of the genome with high concentrations of QTL for various traits called clusters and specific trait Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
129
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 166 publications
(140 citation statements)
references
References 74 publications
7
129
0
2
Order By: Relevance
“…Many markers, such as BNL3255c, NAU1085 and TML21, were associated with several traits. Five QTL clusters in this study resembled those of Said et al 13. (Table 6).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Many markers, such as BNL3255c, NAU1085 and TML21, were associated with several traits. Five QTL clusters in this study resembled those of Said et al 13. (Table 6).…”
Section: Discussionsupporting
confidence: 86%
“…Interestingly, compared the yield-related trait QTLs detected in more than three environments, we also found that the number of QTLs showing negative effects on fiber yield-related traits is much more than that of QTLs showing positive effects (25 negative QTLs:15 positive QTLs) (Supplementary Information Table S1). When comparing our results with those of our previous report17, and a report by Said et al 13. on intraspecific and interspecific populations, for example, we found that seven qBWs, five qLPs and five qSIs had never been reported before.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Said et al [59] comprehensively analyzed 2,134 previously reported QTLs in intra- and inter-species populations and detected numerous QTLs, which were distributed in clusters in certain chromosome regions in the specific populations. In the present study, QTLs controlling different traits were also detected at the same SSR marker locus.…”
Section: Discussionmentioning
confidence: 99%
“…The chromosome segments of these QTL hotspot clusters could be useful for molecular breeding based on common molecular markers [59]. When the chromosome segments clustered both the favorable alleles of the QTLs for cotton fiber quality and yield traits, it could be more easily used for simultaneous improvement of traits.…”
Section: Discussionmentioning
confidence: 99%